Pengembangan Bahan Ajar LKS Elektronik Menggunakan Model Pembelajaran Search Solve Create Share Berbantuan FlipHTML5 pada Materi Mikroprosesor Kelas XI TAV di SMKN 5 Jakarta - Nurmalasari, Siti; Sukardjo, Moch; Bintoro, Jusuf (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2023)
In this study, an electronic LKS teaching material was developed using the Search Solve Create Share (SSCS) learning model assisted by FlipHTML5 on the Microprocessor material for Class XI Audio Video Engineering major at SMKN 5 Jakarta, using the Research and Development research method and the 4D development model consisting of four steps, namely Define, Design, Development and Disseminate, but in this study it was limited to the development stage. The results of the study showed that the electronic LKS used the SSCS learning model developed following the R&D method and the 4D model; LKS feasibility test by material experts, language experts, instructional design experts, media experts with the results of the assessment by the three getting the category "Very Feasible"; LKS trials to students through individual trials and small group trials with LKS assessments getting the category "Very Feasible".